Phenotyping and Genotyping Analyses Reveal the Spread of Puccinia striiformis f. sp. tritici Aeciospores From Susceptible Barberry to Wheat in Qinghai of China - Chen, Wen; Zhang, ZeDong; Ma, Xinyao; Zhang, Gensheng; Yao, Qiang; Kang, Zhensheng; Zhao, Jie (Frontiers in Plant Science, 2021)
Puccinia striiformis f. sp. tritici Eriks., the cause of wheat yellow or stripe rust on wheat, undergoes sexual reproduction on barberry, but it is unclear if barberry plays any role in stripe rust epidemics under natural conditions. P. striiformis f. sp. tritici was isolated from its alternate host barberry(Berberis spp.) and primary host wheat in the vicinity of barberry by inoculation of aeciospores and urediniospores on Mingxian 169 cultivar in Qinghai province of China in 2018. The P. striiformis f. sp. tritici isolates from barberry and wheat were characterized to virulence patterns by inoculation on 24 differentials bearing Yr gene under control conditions and analyzed using 12 polymorphic simple sequence repeat (SSR) markers. The occurrence frequency of P. striiformis f. sp. tritici on barberry was 1.87% by inoculation aecia collected from barberry on Mingxian 169 of wheat. A close virulence relationship was presented between P. striiformis f. sp. tritici isolates from both barberry and wheat based on virulence simple matching coefficient and PCoA. Additionally, the same genetic ancestry, based on Structure and close genetic relationship using DAPC and PCoA, was shared between P. striiformis f. sp. tritici isolates from barberry and those from wheat. Altogether, all results indicated that the role for barberry in providing aeciospores as inoculum source causing wheat stripe rust epidemic in Qinghai in spring is of considerable importance.